Evaluasi Atas Penerapan Akuntansi Murabahah Dalam Kaitannya Dengan Laporan Keuangan - Syahrina, Erna; Rosita, Siti Ita (Jurnal Ilmiah Akuntansi Kesatuan, 2014)
Murabahah financing is one of the Islamic financial institutions to improve their business by mobilizing funds from the public through the provision of goods through trading system where the bank buys goods customer's needs. The sale of goods shall state the cost and benefits agreed upon by the seller and the buyer. The purpose of this study was to evaluate the treatment and application of accounting in Islamic banking murabahah relating to the financial statements. The evaluation was done to determine whether the treatment and application of accounting murabahah in the Islamic banking and has been applied in accordance with PSAK No. 102, as well as the presentation offinancial statements in accordance with PSAK No. 101. Research by the author is in PT. Bank BNI Syariah, Tbk Branch located in Bogor , engaged in the field of Islamic banking. Object of research taken in this study is the product Griya with deferred payment system. In a murabahah transaction tough, Bank BM Syariah will record murabahah receivables and deferred murabahah profit. Murabahah tough realized gains will be recorded upon receipt of installments from the customer. Murabahah receivables that have not been repaid by the customer will be reported on the balance sheet at net relisasi value, while a legitimate murabahah profits realiÃ¦d will be reported in the income statement. Evaluation results in this study that the application of accounting murabahah punch at PT. Bank BM Syariah, Tbk Bogor Branch in accordance with PSAK No. 102 and presentation offinancial statements in accordance with PSAK No. 101. Keyword: murabahah accounting, financial statements